2021
DOI: 10.1055/s-0041-1729753
|View full text |Cite
|
Sign up to set email alerts
|

Human Codon Usage: The Genetic Basis of Pathogen Latency

Abstract: Infectious diseases pose two main compelling issues. First, the identification of the molecular factors that allow chronic infections, that is, the often completely asymptomatic coexistence of infectious agents with the human host. Second, the definition of the mechanisms that allow the switch from pathogen dormancy to pathologic (re)activation. Furthering previous studies, the present work (1) analyzes the frequency of occurrence of synonymous codons in coding DNA, that is, codon usage, as a genetic tool that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 92 publications
(123 reference statements)
0
3
1
Order By: Relevance
“…Trypanosomatids have fewer copies of tRNA genes (fewer isodecoders) (Figure 2A) than vertebrates (74,75), suggesting that these genes may be under selective pressure to avoid deleterious mutations. Here, we detected forty-six anticodons for sixty-two codons (Figure 2D and Supplementary Table 2B), which contrasts with findings in humans, where there are fifty-seven anticodons for sixty-one codons (76,77). This indicates that the parasite needs to employ more strategies to recognize the entire codon repertoire of the genome, such as employing more modifications in anticodons and codonanticodon wobble pairing.…”
Section: Discussioncontrasting
confidence: 78%
“…Trypanosomatids have fewer copies of tRNA genes (fewer isodecoders) (Figure 2A) than vertebrates (74,75), suggesting that these genes may be under selective pressure to avoid deleterious mutations. Here, we detected forty-six anticodons for sixty-two codons (Figure 2D and Supplementary Table 2B), which contrasts with findings in humans, where there are fifty-seven anticodons for sixty-one codons (76,77). This indicates that the parasite needs to employ more strategies to recognize the entire codon repertoire of the genome, such as employing more modifications in anticodons and codonanticodon wobble pairing.…”
Section: Discussioncontrasting
confidence: 78%
“…Defining the relationship(s) between infectious agents and the human host is a crucial topic in immunology, microbiology, and infectious medicine. Although it has been proposed that genetic factors might play a role, 1 2 the exact mechanisms of chronic infections and occasional (re)activation of pathogens in the human host are largely misunderstood and poorly studied. The issue became even more relevant in light of the recent Ebola virus, Dengue virus, and SARS outbreaks associated with high morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…According to this molecular mimicry–oriented paradigm, the research rationale of the present work is based first on the consideration that, due to the numerous peptide commonalities, inhibition of pathogen protein synthesis during latency may represent a host device to avoid potential destructive autoimmune cross-reactions. 30 In the case in point, constraining the expression of EBNA1 would prevent the host immune response against the EBNA1 protein as well as cross-reactive reactions with the host proteins that share peptide sequences with the virus, 27 28 29 thus possibly explaining why EBNA1 protein synthesis is repressed.…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study searches for possible mechanisms underlying the inhibition of EBNA1 protein synthesis on the basis of previous data [30][31][32][33] that suggested that the synthesis of a protein does not occur if the codon usage of the open reading frame (ORF) coding for the protein does not comply with the codon usage of the host. In this regard, data were obtained for the ORFs coding for (re)activation-related proteins from Herpes simplex virus type 1, 30 Toxoplasma gondii, 30 Plasmodium falciparum, 30 Cryptococcus neoformans, 30 Cytomegalovirus (CMV), 31,32 and severe acute respiratory syndrome coronavirus 2. 33 Therefore, as a logical extension of such data, the issues of why and how EBNA1 protein synthesis is restricted/resumed during latency and (re)activation, and the role of EBNA1 GAR have been analyzed through the lens of the compliance to the human codon usage.…”
Section: Introductionmentioning
confidence: 99%